Quality Prerequisites of Fruits for Storage and Marketing - Ahmad, Md Shamsher; Nayyer, Md Abu; Aftab, Ahmar; Nayak, Basant; Siddiqui, Md Wasim (Journal of Postharvest Technology, 2014)
Quality is a major component that attracts consumers of all ages.  If the consumers like it, they are ready to pay a premium price.  India is the second largest producer of fruits in the world.  However, quality of the produce is not up to the world standard  level. There may be many reasons for this, but one of the main  reasons is lack of knowledge. Most producers are small and  marginal farmers and they are not much aware about quality.  Country’s current distribution system of fresh produce is also  inefficient in maintaining quality in the long supply chain  between producers and consumers. With the amendment in the  policy of Agricultural Produce Market Committee, recently a few  reputed companies entered into fruit business on small, medium,  and large-scale. These firms increased quality bars of Indian  fruits as only quality fruits are purchased and sold by these firms.
Keywords: Fruits; Commercial Quality Marketing; Postharvest; Storage; Marketing